Pengaruh Komitmen Kerja, Softskill Dan Spritual Quotient Terhadap Profesionalisme Guru Di SMA Negeri 5 Bukittinggi - Ahda Ahda; Yulihasri Yulihasri; Dona Amelia (Jurnal Visi Manajemen, 2019)
Teacher profession requires certain expertise and skills, where expertise and skills can be obtained from an education or special education training. The reality is that there are still many teachers who have met the qualifications and certified of educators, but their competence is still far from being expected to be able to produce students who have integrative abilities. The purpose of this study was to determine the effect of work commitment, soft skills and spiritual quotient on teacher professionalismat SMA Negeri 5 Bukittinggi in 2020. This type of research is quantitative research. The study was conducted at SMA 5 Bukittinggi. The study population was all teachers, 63 people. Data management in this study will use the smartPLS software. The results of the t statistic test were found to be 2,727greater than the T-table of 1. 999 with a p value of 0.007 smaller than 0. 05. The results of the t-statistic test were 3,629, greater than the T-table 1. 999 with a p value of 0. 000 less than 0. 05. The t-test results obtained by 3,629greater than the T-table 1. 999 with a p value of 0. 039smaller than 0. 05. The demands of teacher professionalism in the modern era must be balanced with the provision of good competencies through various workshops, competency development and also trainings that are followed on an ongoing basis